The role of~micro, small and medium enterprises (MSMEs) to the sustainable development of sub-Saharan Africa and its challenges: A systematic review of evidence from Ethiopia - Ebrahim Endris; Andualem Kassegn (Journal of Innovation and Entrepreneurship, 2022)
Micro, small and medium-sized enterprises (MSMEs) have a potential impact on achieving many of the sustainable development goals much greater than their size. This review aimed to investigate existing literature on the contribution of MSMEs to the sustainable development of Ethiopia and its challenges. The review provides a comprehensive and systematic summary of evidence and provides future research directions. A systematic review methodology was adopted~through~reviewing the available literature~comprehensively including research articles, policy documents, and reports over the period 2011-2021 from ScienceDirect, Google Scholar, ECONBIZ, IJSTOR, EBSCO, Web of Science, and Scopus databases. A search on these databases and grey literature returned 1270 articles; 87 papers were included in this review~following screening of aticles~using pre-determined criteria. The paper found that MSMEs significantly~contributed to the sustainable development goals of Ethiopia through creating employment, alleviating poverty, and improving their living standards. However, the review has identified access to finance, access to electricity, and trade regulation are the major constraints for the development of the sector. The review outlines key policy implications to develop a comprehensive policy that alleviates the existing challenges of the sector and calls for further MSMEs impact evaluation research.
Keywords: 650; Employment; Enterprises; Ethiopia; Finance; Sustainable development